A Design and Testing of Electrosurgery Unit - Safitri, Meilia; Pranata, Adrian; Irfan, Muhammad; Ibrahim, Muhammad Hamka (Journal of Fuzzy Systems and Control, 2023)
Bleeding during surgery is common in major surgical operations. So, it is not recommended to make an incision using a conventional scalpel. As an alternative to replacing a conventional scalpel, an electric scalpel or know as electrosurgery unit (ESU) is made by utilizing a high frequency whose duty cycle can be adjusted and then being focused on one point is a solution to prevent bleeding. This research will design a bipolar electric scalpel or bipolar electrosurgical unit with a frequency of 210-250 KHz and an input voltage of 50-90 VDC to perform pure cuts on chicken meat samples. The box pulse frequency will be generated from IC 4069. The output of the oscillator generator will read the high and low voltage on the Arduino Nano digital pin. The current will be amplified at the oscillator output and then processed in the inverter driver circuit. The selection of the DC input voltage will use a voltage driver circuit. The inverter driver output and voltage driver will be step-up to get a maximum power of 10.4W with a resistance of 100Ω at a frequency setting of 210 KHz and an input voltage of 90 VDC and a minimum power of 1.4W with a resistance of 100Ω at a frequency setting of 250 KHz and input voltage 50 VDC.